A Cuckoo Search Based Pairwise Strategy For Combinatorial Testing Problem - Kamal Z., Zamli; Nasser, Abdullah B.; AlSariera, Yazan A.; Al-Sewari, Abdul Rahman Ahmed Mohammed (JATIT & LLS, 2015)
Combinatorial Testing (CT) is a sampling technique to generate test cases with a focus on the behavior of interaction system's components with their collaborators. Given its effectiveness to reveal faults, pairwise testing has often been chosen to perform the required sampling of test cases. The main concern for pairwise testing is to obtain the most optimal test sets (i.e. pairwise dictates that every pair of input values is covered by a test case at least once). This paper discusses the design and implementation a new pairwise strategy based on Cuckoo Search, called Pairwise Cuckoo Search strategy (PairCS). PairCS serves as our vehicle to investigate the usefulness of Cuckoo Search for pairwise testing.